1997
DOI: 10.1111/j.1432-1033.1997.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Trypanothione Reductase

Abstract: Trypanothione redutase, one of the family of flavin-dependent disulfide oxidoreductases, catalyses the reduction of trypanothione disulfide [N1,N1'-bis(glutathionyI)spermidine] and related glutathionyl-polyamine disulfides. A series of subtly different, designed substrate analogues based on trypanothione were prepared by means of a solid-phase approach and used to study the catalytic efficiency of the parasitic enzyme. Kinetic analysis showed that the size of the polyamine bridge was relatively unimportant, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Trypanothione homologues like homotrypanothione and nortrypanothione are however rather efficient substrates with k cat /K m only slightly lower than trypanothione [80]. Deleting one glutamic acid residue reduce the efficiency: N 1 -acetylcysteinylglycyl-N 8 -glutathionylspermidine and N 8 -acetylcysteinylglycyl-N 1 -glutathionylspermidine are 10 times less efficicient as a substrate than trypanothione.…”
Section: Trypanothione Reductasementioning
confidence: 97%
“…Trypanothione homologues like homotrypanothione and nortrypanothione are however rather efficient substrates with k cat /K m only slightly lower than trypanothione [80]. Deleting one glutamic acid residue reduce the efficiency: N 1 -acetylcysteinylglycyl-N 8 -glutathionylspermidine and N 8 -acetylcysteinylglycyl-N 1 -glutathionylspermidine are 10 times less efficicient as a substrate than trypanothione.…”
Section: Trypanothione Reductasementioning
confidence: 97%
“…2). 11 GR has a hydrophilic, positively charged region in its active site that interacts with the glycine carboxylates of glutathione disulfide, while TR has a larger binding site with a negatively charged region with which the spermidine moiety of trypanothione disulfide binds. 12 The absence of TR from the mammalian host and the sensitivity of trypanosomatids to oxidative stress makes TR an attractive target for trypanosomiasis therapeutics.…”
mentioning
confidence: 99%
“…TR and human GR have similar catalytic mechanisms; 14 of the 19 amino acid residues close to the binding site are conserved. However, they are specific to their respective disulfide substrates (36) (Fig. 1B).…”
mentioning
confidence: 99%
“…1C). Studies of the substrate specificity of TR have found that the active site tolerates noncognate substrate architecture and removal of the disulfide moiety (36), such that a number of nonreducible acyclic and cyclic substrate analogues (13) display TR inhibition. Polyamine-and peptide-based TR inhibitors are generally structurally related to spermine and spermidine and have been shown to be effective competitive inhibitors (32).…”
mentioning
confidence: 99%